Experimental and numerical study of a printed circuit heat exchanger. (November 2016) - Chen, Minghui; Sun, Xiaodong; Christensen, Richard N.; Shi, Shanbin; Skavdahl, Isaac; Utgikar, Vivek; Sabharwall, Piyush
Highlights: A dynamic model is developed for transient analysis of the straight-channel PCHE. Transient scenarios of the straight-channel PCHE subject to helium temperature and mass flow rate variations are numerically investigated. Steady-state temperature distribution inside the straight-channel PCHE is obtained in calculation. Experiments are conducted to study the dynamic behavior of the straight-channel PCHE. Abstract: Printed circuit heat exchangers (PCHEs) are promising to be employed in very-high-temperature gas-cooled reactors (VHTRs) due to their high robustness for high-temperature, high-pressure applications and high compactness. PCHEs typically serve as intermediate heat exchangers (IHXs) that isolate the secondary loop from the reactor's primary system and hence must be sufficiently robust to maintain the system integrity during normal and off-normal conditions. In addition, the performance of the PCHE-type IHX could considerably affect the nuclear power plant overall operation since any transients on the secondary side would be propagated back to the reactor's primary coolant system via the IHX. It is therefore imperative to understand how the PCHE would dynamically respond to a variety of transients. In the current study, experiments were first conducted to examine the steady-state thermal performance of a reduced-scale straight-channel PCHE. A dynamic model benchmarked in a previous study was then used to predict the steady-state and transient behavior of the PCHE. The steady-state temperature profiles of the working fluids on both the hot and cold sides and in the solid plates of the heat exchanger were obtained, which served as the initial condition for the transient simulations. The detailed dynamic response of the straight-channel PCHE, subject to inlet temperature variations, helium mass flow variations, and combinations of the two, was simulated and analyzed. In addition, two sets of transient tests, one for helium inlet temperature increase and the other for helium inlet temperature decrease, were experimentally carried out to assess the applicability of the dynamic model. Comparisons of the numerical results with the experimental data show that the dynamic model is successful in predicting the experimental transient scenarios. Although difference was observed between the numerical results and experimental data, the comparisons suggest that the numerical solutions are sufficiently accurate and conservative and that the applicability of the dynamic model proposed for predicting the steady-state and transient performance of the straight-channel PCHE has been confirmed. Furthermore, both the numerical and experimental studies provide insights into the dynamic performance of the PCHE.